The relationship of poetry to painting at Al-Jahith - Hindi, Tanweer bint Ahmed (Journal of Humanities & Social Sciences, 2017)
The relationship between poetry and other arts is not hidden, and from those human arts to which poetry has a strong relationship is (drawing). The relationship between these two arts is as old as the art itself. It has found many references to this relationship in our critical heritage. Al-Jahiz is the oldest Arabic critic who exposed this relationship and highlighted it through the practical application in his critical studies. Therefore, I saw the importance of shedding light on his position on this important issue and trying to identify the extent to which he applied his perception, to consolidate this relationship in our critical Arabic heritage through the pyramid of the ancient Arabic criticism (Al-Jahiz). This was done by following the three scientific methods: inductive, descriptive, and applied. Al-Jahiz dealt with this issue by commenting on the poetic verses that contain graphic images, such as imitation, metaphor, and metonymy in his both books: Al-Bayan Wal-Tabyeen, and Al-Hayawan. The research did not overlook the effect of the relationship between poetry and drawing on the great critical issue (word and meaning) through the criticism of Al-Jahiz. The research reached that Al-Jahiz was very aware of the relationship between the human arts and their interactions, and that poetry is based on depiction. Al-Jahiz is the first Arabic critic to say that there is an authentic relationship between poetry and drawing. He draws the attention of the rhetoricians and critics after him to the literary depiction, the ability of poetry to represent the meanings to the senses, and the played role by visual perceptions in the processes of formatting and receiving poetry. The poet and the painter agree initially on the imagination which they come out, and then they differ in the tools and the body they produce to meet eventually again when they have the same effect - often - on the recipient.